Molten salt assisted synthesis of 3C–SiC nanowire and its photoluminescence properties. Issue 10 (December 2015) - Zhang, Ju; Li, Wei; Jia, Quanli; Lin, Liangxu; Huang, Juntong; Zhang, Shaowei
Abstract: Single crystalline silicon carbide nanowires (SiC NWs) were prepared through the carbothermal reduction route using silica fume and phenolic resin in a molten salt (NaCl and NaF) medium at 1450 °C. The presence of molten salts was found to have a noticeable effect on the complete conversion of SiO2 to 3C–SiC with the temperature increasing from 1300 °C to 1450 °C, and NaF/NaCl ratios and molten salts/reactant ratios also played vital roles in the growth of SiC NWs. The as-achieved SiC NWs were 100–150 nm in diameter and 10 μm in length, which grew along the direction perpendicular to the (111) plane and contained stacking faults (SFs). The as-synthesized SiC NWs had a strong emission peak (422 nm) located in the violet–blue spectral range, suggesting potential applications in optoelectronic devices. All these discoveries suggest a cheap and feasible route for large scale growth of high quality SiC NWs at low temperature.